Thricho‐rhino‐phalangeal syndrome and severe osteoporosis: A rare association or a feature? An effective therapeutic approach with biphosphonates. Issue 3 (19th December 2013) - Macchiaiolo, M.; Mennini, M.; Digilio, M.C.; Buonuomo, P.S.; Lepri, F.R.; Gnazzo, M.; Grandin, A.; Angioni, A.; Bartuli, A.
<x xml:space="preserve">Abstract</x> Trichorhinophalangeal syndrome (TRPS) is a rare, autosomal dominant malformation syndrome characterized by hair, craniofacial and skeletal abnormalities, skin laxity, deformation of phalanges and anomalies of pelvis, femurs, and tibias. Three subtypes have been described: TRPS I, caused by mutations in TRPS1 gene on chromosome 8; TRPS II, a microdeletion syndrome affecting the TRPS1 and EXT1 genes; and TRPS III, a form with severe brachydactyly, due to short metacarpals, and severe short stature, but without exostoses. We present the case of a 7‐year‐old boy, affected by TRPS with a severe osteoporosis and several spontaneous bone fractures, an association described only once in the literature, successfully treated with biphosphonates. Bone mineral density (BMD) at dual‐energy X‐ray Absorptiometry (DXA) was of 0.331 g/cm2 at lumbar spine with. He had four spontaneous femoral fractures in a year, and for this reason he was been operated for positioning intramedullary osteosynthesis and orthopedic supports. Due to the severity of the clinical and radiological pattern it was established, after approval of the Ethical Committee, to begin off‐label therapy with infusions of neridronate at a dose of 2 mg/kg IV every 3 months. The treatment was, in this patient, effective both in terms of clinical (absence of new fractures) and mineralomethric (+45% BMD ath the lumbar level). We therefore suggest that treatment with biphosponates can be taken in account as a possible therapeutic option in case of bone fragility in patients with TRPSI. © 2013 Wiley Periodicals, Inc.